Answer :

Answer:

According to the question the answer should be : [tex]\frac{-2}{3}[/tex]

Step-by-step explanation:

[tex]-\frac{1}{9} -\frac{5}{9}[/tex]

[tex]=\frac{-1}{9}-\frac{5}{9}[/tex]

[tex]=\frac{-1}{9} +\frac{-5}{9}[/tex]

[tex]=\frac{-2}{3}[/tex]

You should be getting the final answer as : [tex]\frac{-2}{3}[/tex]

Answer and Step-by-step explanation:

The solution to this question : [tex]\frac{-2}{3}[/tex]

Step 1 : Remove the parentheses  :

[tex]= -\frac{1}{9} -\frac{5}{9}[/tex]

Step 2 : Since the denominators are equal, combine the fractions :

[tex]=\frac{-1-5}{9}[/tex]

Step 3 : Subtract the numbers :

[tex]-\frac{6}{9}[/tex]

Step 4 : Now, cancel the common factor (3) :

[tex]=-\frac{2}{3}[/tex]